Biomechanical services and research for athletes and coaches to enhance performance and prevent injury - Brown, N. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Athleticism, sport-specific ability, rigorous training supervised by expert coaches and well supported daily training environments are the main determinants of success in international sporting competition (Bosscher et al., 2010). Sport Biomechanists contribute to the training environment largely by identifying and advising on movement technique. This service provides understanding of the mechanical basis of sport-specific performances and injury. However, a kinematic description of technique is often not sufficient to identify improper skill execution. Cycling presents an example where kinematic variability is low, but where underlying force application on the bicycle`s pedals and joint-specific powers during pedalling can vary. Such analyses provide a deeper understanding of potential mechanisms underlying injury and athletic performance.